Artificial Intelligence (AI) Implementation in the Field of Public Administration in the Era of the Industrial Revolution 4.0 in Indonesia - Kurhayadi, Kurhayadi (International Journal of Demos (IJD), 2022)
AbstractArtificial intelligence is one of the products of the industrial revolution 4.0, whose development and use have been widely used in everyday life and many sectors. Artificial intelligence is used to improve public services by providing technology-based applications in public administration. This research will investigate the extent to which artificial intelligence has been implemented in the field of public administration, the impact of artificial intelligence's implementation in the field of public administration, and the preparedness of government human resources (HR) in the application of artificial intelligence. This study will employ a qualitative methodology. The data used in this study came from a variety of prior studies that are still relevant to this investigation. This study revealed that artificial intelligence can have a favorable impact on the government's ability to provide quality public services. But unfortunately, the capability of artificial intelligence cannot be implemented in all regions of Indonesia due to the problem of inadequate resources.Keywords: Industrial Revolution, Public Administration, Artificial Intelligence (AI), Implementation.Â AbstrakKecerdasan buatan merupakan salah satu produk revolusi industri 4.0 yang perkembangan dan penggunaannya telah banyak digunakan dalam kehidupan sehari-hari dan banyak sektor. Kecerdasan buatan digunakan untuk meningkatkan pelayanan publik dengan menyediakan aplikasi berbasis teknologi dalam administrasi publik. Penelitian ini akan mengkaji sejauh mana implementasi kecerdasan buatan di bidang administrasi publik, dampak penerapan kecerdasan buatan di bidang administrasi publik, dan kesiapan sumber daya manusia (SDM) pemerintah dalam penerapan kecerdasan buatan. Penelitian ini akan menggunakan metodologi kualitatif. Data yang digunakan dalam penelitian ini berasal dari berbagai penelitian terdahulu yang masih relevan dengan penelitian ini. Studi ini mengungkapkan bahwa kecerdasan buatan dapat memberikan dampak yang menguntungkan bagi kemampuan pemerintah untuk menyediakan layanan publik yang berkualitas. Namun sayangnya, kemampuan kecerdasan buatan tersebut belum dapat diterapkan di seluruh wilayah Indonesia karena masalah sumber daya yang belum memadai.Kata Kunci: Revolusi Industri, Administrasi Publik, Artificial Intelligence (AI), Implementasi.